2022
DOI: 10.1186/s13287-022-02863-7
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus repair: up-to-date advances in stem cell-based therapy

Abstract: The meniscus is a semilunar fibrocartilage between the tibia and femur that is essential for the structural and functional integrity of the keen joint. In addition to pain and knee joint dysfunction, meniscus injuries can also lead to degenerative changes of the knee joint such as osteoarthritis, which further affect patient productivity and quality of life. However, with intrinsic avascular property, the tearing meniscus tends to be nonunion and the augmentation of post-injury meniscus repair has long time be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 136 publications
(134 reference statements)
0
4
0
2
Order By: Relevance
“…Its potential to regenerate adjacent tissue and therefore differentiate into chondrocytes and their ability to produce bioactive molecules such as growth factors and cytokines that modulate a cascade of intrinsic responses of repair mechanisms thus promoting wound healing. 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its potential to regenerate adjacent tissue and therefore differentiate into chondrocytes and their ability to produce bioactive molecules such as growth factors and cytokines that modulate a cascade of intrinsic responses of repair mechanisms thus promoting wound healing. 37…”
Section: Resultsmentioning
confidence: 99%
“…Its potential to regenerate adjacent tissue and therefore differentiate into chondrocytes and their ability to produce bioactive molecules such as growth factors and cytokines that modulate a cascade of intrinsic responses of repair mechanisms thus promoting wound healing. 37 Both scaffolds demonstrated superiority over the empty defect group, indicating that the use of the polymeric scaffold as a meniscus implant favored the preservation of articular cartilage. In particular, the implantation of PLDLA-TMC with MSCs which showed the best outcome, resulted in repair quite equal to the untouched negative control.…”
Section: In Vivo Microscopy Evaluationmentioning
confidence: 95%
“…A eficácia dessa estratégia está intrinsecamente atrelada à capacidade de produzir scaffolds que reflitam tanto a matriz extracelular natural dos meniscos quanto a sua forma macroscópica singular. Diante deste desafio, a bioimpressão 3D emergiu como uma técnica com potencial significativo para a regeneração meniscal 42,43 .…”
Section: Meniscos Do Joelhounclassified
“…Compared with autologous cells and xenogenic cells, stem cells may be a more promising cell source in the field of meniscus regeneration research ( Zhou et al, 2022 ). Multiple studies reported that stem cells are useful in replacing the injured meniscus and restoring its native function when combined with tissue engineering ( Jacob et al, 2021 ; Bian et al, 2022 ). Basing in vitro and in vivo experiments, Li et al proved that Apt/GF-scaffolds increased neomeniscal formation in rabbit critical-sized meniscectomies through mesenchymal stem cell (MSC)-specific recruitment ( Li H. et al, 2022 ).…”
Section: Meniscus Regeneration Hydrogelsmentioning
confidence: 99%